2010
DOI: 10.1364/ol.35.001007
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser fabricated fiber Bragg grating in microfiber for refractive index sensing

Abstract: Fiber Bragg grating (FBG) is fabricated in the microfiber by the use of femtosecond laser pulse irradiation. Such a grating can be directly exposed to the surrounding medium without etching or thinning treatment of the fiber, thus possessing high refractive index (RI) sensitivity while maintaining superior reliability. The grating in the microfiber may have a number of propagation modes in its transmission spectrum, depending on the fiber diameter, and the higher order of mode has larger RI sensitivity. The RI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(113 citation statements)
references
References 19 publications
2
111
0
Order By: Relevance
“…2(b) we can see that the resonant wavelength of FBG in a 35 m diameter fiber has a blue shift versus the FBG in an SMF fabricated with the same laser and phase mask. This is because a thinner fiber leads to a drop in the effective refractive index of the modes propagating in the fiber, thus a decrease in  B , which can be derived from the Bragg condition [10]: …”
Section: Inscription Of Fbg In Microfibermentioning
confidence: 99%
See 1 more Smart Citation
“…2(b) we can see that the resonant wavelength of FBG in a 35 m diameter fiber has a blue shift versus the FBG in an SMF fabricated with the same laser and phase mask. This is because a thinner fiber leads to a drop in the effective refractive index of the modes propagating in the fiber, thus a decrease in  B , which can be derived from the Bragg condition [10]: …”
Section: Inscription Of Fbg In Microfibermentioning
confidence: 99%
“…Fiber sensors, based on the various fiber components, have been developed in many forms [4][5][6][7][8][9], and are exhibiting outstanding performances in the field of physical and bio-chemical sensing. Fiber Bragg grating (FBG) is among the most important optical components which has a wide variation of applications [10][11][12][13]. Here we fabricate an FBG in the microfibers with diameter down to several micrometers, and the temperature and strain responses of the microfiber FBG are investigated by the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Several fabrication techniques such as CO 2 laser irradiation [147], excimer laser irradiation [149,150], femtosecond laser exposure [151], etched corrugations [21], and focused ion beam milling [134-136, 152, 153], have been demonstrated to write gratings directly on as-drawn MNFs. Here we categorize typical MNF gratings into three types:…”
Section: Mnf Mzismentioning
confidence: 99%
“…In 2005, relying on a wet chemical etch-erosion procedure, Liang et al fabricated an MNFBG out of a 6-μm-diameter silica MNF, and used the MNFBG for index measurement in liquids [21]. Later in 2010, using femtosecond laser pulse irradiation, Fang et al reported an MNFBG based on a 2-μm-diameter MNF, which was used for RI measurements with a maximum sensitivity of 231.4 nm/RIU at a RI value of 1.44 [151]. Around the same time, Zhang et al reported a MNFBG written in a photosensitive microfiber using KrF excimer laser, and demonstrated a sensitivity of 102 nm/RIU at a RI value of 1.378 in a 6-μm-diameter MNF [149].…”
Section: Mnf Mzismentioning
confidence: 99%
“…Even optical nonlinear behavior -such as optical bistability and self-switching [12][13][14][15][16][17][18] is also difficult to observe under continuous-wave (CW) or quasi-CW excitation because the extremely high threshold power, which -without optimization -amounts to ~10 4 W. However, MNFs open new opportunities for research. With the emergence of low-loss MNFs, numerous techniques to inscribe gratings into MNFs have been successfully demonstrated over the past five years, for example, processing with an ultraviolet laser [19], a CO 2 laser [20], and a femtosecond laser [21]; and milling with a focused ion beam (FIB) [22]. With these gratings' very small cross-sectional area and their enhanced light intensity, the scale of radiation pressure is sufficient for creating a considerable longitudinal deformation in the structure, which thereby affects the optical characteristics of the grating.…”
mentioning
confidence: 99%